Work-Life Balance dan Work Engagement untuk Mengatasi Stress dan Burnout Anggota Kepolisian Resort Demak Selama dan Pasca Pandemi Covid-19 - Johan Valentino Nanuru; Hardi Warsono; Retno Sunu Astuti; Teuku Afrizal (PERSPEKTIF, 2023)
Since the corona virus entered Indonesia in early March 2020, this virus has spread very quickly. So that the government determines the status of a pandemic situation in the territory of this country. In particular, Polri has the duty to maintain public order and security, carry out law enforcement functions and provide protection, protection and service to the community. This study aims to obtain an overview of; (i) work-life balance that is formed in the work environment of the Demak Resort Police; (ii) work engagement that develops among members of the Demak Resort Police; (iii) work-life balance and work engagement built in the work environment. This research is a descriptive qualitative research with the research locus at the Demak Police Resort. There are two sources of data in this study. Primary data sources were obtained from interviews with seven police officers who were determined by purposive sampling. Secondary data sources are data obtained from electronic journals, reports and e-books. This study found that although members of the Demak Resort Police experienced stress and burnout during the pandemic, all subjects stated that family support and understanding shown by the leadership were factors that greatly assisted the subjects in overcoming the stress and burnout they experienced. Families and leaders have provided support for research subjects to develop a work-life balance in their daily work. The work-life balance that they feel makes police officers give a strong commitment to the tasks assigned to them (work-engagement is built).